O02 Low birthweight is associated with decreased grip strength and reduced leg muscle mass in middle age: findings from the UK Biobank imaging enhancement. (26th April 2021) - Curtis, Elizabeth M; D'Angelo, Stefania; Ashai, Shanze; Ward, Kate; Raisi-Estbragh, Zahra; Petersen, Steffen; Cooper, Cyrus; Harvey, Nicholas C
Abstract: Background/Aims Low birthweight has been shown to be associated with poorer musculoskeletal health in later life in a variety of epidemiological studies. We investigated relationships between birthweight and magnetic resonance imaging (MRI) measures of muscle volume, and between birthweight and measures of grip strength in UK Biobank. Methods UK Biobank is a large prospective cohort of men and women aged 40-69 years, including a detailed baseline assessment in which birthweight was collected by self-report. A subset of participants underwent MRI examination with the dual-echo Dixon Vibe protocol, from neck to knees. Automated body composition analysis was performed using the AMRA Profiler TM system, to segment and quantify total thigh muscle volume. Grip strength was assessed using a Jamar hydraulic hand dynamometer. Associations between birthweight, and thigh muscle volume or grip strength (expressed as Fisher-Yates z-scores) were investigated using multivariate linear regression analysis. This study was conducted under generic ethics approval (NRES:11/NW/0382). Results 13, 048 participants [5, 508 men, mean (SD) age 61.9 (7.6) years and 7, 540 women, age 60.9 (7.2) years] were able to recall their birthweight and underwent MRI body composition analysis or had a measurement of grip strength. In both men and women, higher birthweight was associated with greater thigh muscle volume (adjusted for age and body mass index (BMI)): men, β (95% CI): 0.23 (0.16, 0.30) SD/kg, p < 0.001; women, β (95% CI): 0.28 (0.22, 0.35) SD/kg, p < 0.001. Higher birthweight was also associated with higher grip strength (adjusted for age and height); men, β (95% CI): 0.09 (0.06, 0.13) SD/kg, p < 0.001; women, β (95% CI): 0.06 (0.02, 0.09) SD/kg, p = 0.001. All associations were robust to additional adjustment for current smoking and physical activity. Conclusion Birthweight was positively associated with MRI measures of thigh muscle volume and grip strength in a population of middle-aged UK adults. These findings provide novel evidence in support of the developmental programming hypothesis and suggest that interventions to optimise birthweight may help to prevent sarcopenia and reduce the risk of falls in future generations. (Project 3593) Disclosure E.M. Curtis: None. S. D'Angelo: None. S. Ashai: None. K. Ward: None. Z. Raisi-Estbragh: None. S. Petersen: None. C. Cooper: None. N.C. Harvey: None.